Understanding the molecular conformations of Na-dimyristoylphosphatidylglycerol (DMPG) using DFT-based method - Mishra, Deepti; Pal, Sourav; Krishnamurty, Sailaja (Molecular Simulation, 2011)
The molecular conformations of phospholipids comprising a lipid bilayer determine the physico-chemical properties of the latter. In this study, we attempt to understand the various possible conformations available for an anionic lipid molecule dimyristoylphosphatidylglycerol (DMPG) with Na as its charge-compensating cation. The various possible molecular orientations available for lipid molecule are analysed using a density functional theory-based method. Our study reveals a rich conformational space with two different types of glycerol body orientations, more commonly known as rotamers. Interestingly, this is in agreement with the molecular conformations proposed earlier by NMR studies on lipid monomer solutions. We demonstrate that these conformations are an outcome of delicate balance of electrostatic and van der Waals forces along with intra-molecular hydrogen bonds achieved by a critical combination of torsion angles. Na(+) ions are seen to interact predominantly with the oxygen atoms of the glycerol groups in tail and head along with that of phosphate oxygen atoms leading to a cage-like orientation of lipid molecule around the Na(+). Following the conformational analysis, we attempt to evaluate the electronic properties of few low-lying conformations. This study shows that though the water molecules screen the Na-O(lipid) interactions, they do not dramatically modify the Na-O(lipid) bond distances. The lipid conformation retains the cage-like structure around the Na(+) in the presence of water molecules. Some amount of charge transfer from the water molecules to Na ion is noted. The water molecules modify the phosphate-tail glycerol group interactions leading to a more stable Na-DMPG-H(2)O and Na-DMPG-4H(2)O complexes.
Keywords: DFT; DMPG; molecular conformations; rotamer and hydration energy

Mechanistic investigations on the catalytic transfer hydrogenation of lignin-derived monomers over Ru catalysts: theoretical and kinetic studies - Khan, Tufeil Sartaj; Singh, Dheerendra; Samal, Pragnya Paramita; Krishnamurty, Sailaja; Dhepe, Paresh Laxmikant (ACS Sustainable Chemistry & Engineering, 2021)
The hydrodeoxygenation (HDO) reaction of oxygenated compounds such as lignin-derived phenolics is well studied using molecular H-2 as a hydrogen source, yet the use of high pressures discourages its use on an industrial scale. As an alternative, the catalytic transfer hydrogenation (CTH) pathway provides in situ hydrogenation species, which reduces the need for the high-pressure infrastructure required when molecular hydrogen is used. Nevertheless, this strategy is scantly studied, and in lieu with this, herein we report the kinetic and mechanistic investigations of the CTH strategy for the HDO of guaiacol, phenol, anisole veratrole, and eugenol to their respective products. For potential commercialization purposes, low loading of metal, milder reaction conditions, and high selectivity toward desired products with a high H/C ratio were considered while designing catalysts (0.5 wt % Ru on SiO2-Al2O3, SiO2, Al2O3-acidic, Al2O3-basic, and Al2O3-neutral) for these reactions. As high as 74% cyclohexanol yield from guaiacol was achieved at 225 degrees C in the presence of isopropyl alcohol (IPA) as the hydrogen source and over the Ru/Al2O3-acidic catalyst reduced at 150 degrees C. A detailed kinetic study is carried out to understand the interaction of the substrate and intermediates with the catalyst and the influence of reaction parameters on the product formation. It was observed that the cisisomer of 2-methoxycyclohexanol rapidly undergoes further conversion than the trans-isomer. The experimental observations are substantiated through density functional theory (DFT) studies on Ru(0001) and guaiacol molecule complexes. DFT studies indicate that the adsorption of the cis-isomer is more exothermic as compared to that of the trans counterpart, and the underlying electronic factors are elucidated using charge density difference and density of states plots.
Keywords: catalytic transfer hydrogenation; Cyclohexanol; DFT; Hydrodeoxygenation; kinetics; lignin monomers; Supported metal catalysts

Substrate augmented catalytic activity towards NRR: a case study of Li doped Al clusters on defective graphene - Samal, Pragnya Paramita; Poonam; Krishnamurty, Sailaja (2021)
Density Functional Theory (DFT) based methods are applied to examine the potential of lithium doped aluminium clusters consisting of 3-13 atoms for dinitmgen molecule activation in terms of N N bond length, redshift in N N bond stretching frequency, nitrogen interaction energy and frontier molecular orbitals analysis. The present work highlights the role of monovacant C-3 defective graphene as a support in fine tuning the catalytic activity of Li doped Al clusters for reduction of N-2. Fundamental insights to synergic binding of clusters with defective graphene is brought out and its role in enhancing activation of dinitmgen molecule is explained. Supported Aln-1Li clusters with six or more atoms are noted to be more active towards N-2 molecule activation as compared to the clusters without support. Dinitrogen molecule undergoes a maximum bond elongation of 1.56 angstrom corresponding to redshift of 1690 cm(-1) on Al7Li@graphene and Al12Li@graphene. This is maximum value reported in context of activation for N-2 molecule till date.
Keywords: Al clusters; Al12Li; C-3 defective graphene; DFT; Li Doping; N-2 activation; Red-shift

Structure-property insights into chiral thiophene copolymers by direct heteroarylation polymerization - Nikam, Shrikant B.; Singh, Chandrodai Pratap; Krishnamurty, Sailaja; Asha, S. K. (European Polymer Journal, 2022)
Chiral thiophene copolymers with fluorene as co monomer are designed having N-Boc-L-glutamic acid-1-tert-butyl ester as a chiral substituent located either on the thiophene unit or the fluorene unit with varying spacer length. The atom-economic direct heteroarylation polymerization (DHAP) method is utilized for the polymerization. Gibb's free energy (delta G) for polymerization determined using DFT calculations indicate difficulty in achieving high molar mass when the bulky chiral substituents are attached through short spacer to the backbone. The experimental observations are in agreement with the theoretical calculations with no polymer-ization or very low molar mass sticky compounds obtained for reactions with predicted + & UDelta;G values. Structure -property relationship are compared for two chiral polymers -P4 and P5 having the chiral substitution on thiophene and fluorene units respectively. No CD signal is observed in THF-a good solvent where the polymers are molecularly dissolved. Intense bisignated CD signal is observed for both polymers upon addition of methanol - a poor solvent, to their THF solution. The bisignate CD signal with maxima at lower wavelength and inflection point associated with the pi-pi* absorption band is characteristic of exciton coupling between polymer chains in a left handed helical orientation. Small differences are observed in the intensity of the CD signal for the polymers P4 and P5 highlighting the impact of steric hindrance of bulky pendant groups on polymer conformation. DHAP is an atom economic polymerization procedure that can be gainfully utilized for developing chiral conjugated polymers.
Keywords: chiral; DFT; Direct heteroarylation polymerization; Gibb?s free energy; Steric Hindrance

Understanding the thermal stability of a 3d, 4d, and 5d element doped aluminium nanocluster through BOMD simulations - Samudre, Nikhil S.; Singh, Chandrodai Pratap; Krishnamurty, Sailaja (Molecular Simulation, 2023)
Endohedrally doped atomic clusters have generated considerable interest among computational chemists on account of their tunable chemical properties that mimic a super atom. Such endohedrally doped clusters have also been experimentally realised in the more recent past. The present work explores the practical existence of 3d, 4d and 5d doped aluminium clusters, more specifically doped Al13 cluster, by evaluating systematically their structural stability through the first principle molecular dynamical simulations. Born-Oppenheimer Molecular Dynamics (BOMD) simulations have been carried out on Al12X atomic clusters where X = Ti, V, Fe, Co, Ni, Cu, Zn, Y, Mo, Ru, Rh and W are in endohedral position. The thermal stability of such endohedrally doped clusters is quantified through parameters such as delta(rms), MSD and is an element of(pro). Electronic structure calculations reveal that endohedral doping of only Rh, Cu and Zn is preferred in the Al-13 cluster. Other dopants prefer to remain on the surface positions. However, finite temperature calculations reveal that the Al12Zn cluster undergoes surface modifications from 300K leading to a distorted icosahedral structure. Al12Cu cluster in quartet spin state is the only thermally stable cluster with Cu remaining in the endohedral position and structure retaining icosahedral confirmation till 700K.
Keywords: Al-13 atomic cluster; BOMD simulations; DFT; Endohedral doping; super atom

In silico designing of electrocatalysts for hydrogen evolution reaction: a focus on titanium metal-based diboride monolayers - Shivankar, Bhavana R.; Verma, Tushar Singh; Krishnamurty, Sailaja (International Journal of Hydrogen Energy, 2025)
Enhancing the efficiency of Hydrogen Evolution Reaction (HER) using chemically modified electrocatalytic titanium diboride surfaces with transition metal-based Single Atom Catalysts (SACs) is illustrated using Density Functional Theory (DFT) based methods employing solvent effects. With higher surface concentrations of nonmetal boron rather than titanium metal, these highly conductive, extremely hard, chemically, and thermally stable electrocatalysts are more cost-effective and superior to their MBene analogs. A systematic analysis of these transition metal-based SACs from the 3d, 4d, and 5d groups embedded in TiB2 monolayer for its HER activity reveals the reduction in limiting potential. As the most effective SAC for improved HER, Zn@TiB2 SAC has a limiting potential of 0.08 eV in acidic and 0.21 eV in alkaline media. The higher exchange current density of Zn@TiB2 (5.74 x 10-5 A cm-2), which exceeds most previously reported electrocatalysts, indicates exceptional HER performance. This work shows that transition metal boride electrocatalysts are economically viable for HER and pave a path for experimentalists.
Keywords: AIMD; D -band center; DFT; HER; SAC